210k views
0 votes
Determine the rate of change for y = √3x - 1Decreasing at an increasing rateO Increasing at a decreasing rateO Constant increasing rateO Decreasing at a decreasing rate

Determine the rate of change for y = √3x - 1Decreasing at an increasing rateO Increasing-example-1
User BrDaHa
by
5.3k points

1 Answer

4 votes

Given:


y=√(3x-1)

Required:

We need to find the rate of change of the given equation.

Step-by-step explanation:

Consider the given equation.


y=√(3x-1)

Differentiate with respect to x.


(dy)/(dx)=(1)/(2)(1)/(√(3x-1))*3
(dy)/(dx)=(3)/(2√(3x-1))


(dy)/(dx)=(3)/(2√(3x-1))>0
The\text{ function is increasing}

We know that dy/dx is the rate of the given function.

Differentiate dy/dx with respect to x.


(d^2y)/(dc^2)=-(1)/(2)*(3)/(2(3x-1)^(3\/2))*3
(d^2y)/(dc^2)=(-9)/(4(3x-1)^(3\/2))<0
The\text{ rate is decreasing}

The function is increasing, and the rate is decreasing.

Final answer:

Increasing at a decreasing rate.

User Thechmodmaster
by
5.6k points